Business incubators in Brazil: realities and challenges - Ribeiro, Priscilla Cristina Cabral; Alves de Matos Freire, Kyane; Chudoba, Katherine M; Borges Renault, Thiago (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose - The purpose of this paper is to describe five business incubators in Brazil through the Triple Helix model, their realities and challenges. Theoretical framework – A discussion of Business incubators, Triple Helix and the use of Information and Communication Technologies in incubators are the main lenses used to support the research. Design/methodology/approach – For this purpose, five case studies of incubators in the Northern and Southern Regions of Brazil were used. The paper uses a qualitative approach and collects data through semi-structured interviews. To analyze the results, the theory was compared to the findings from the field research. Findings - The results showed that most incubators are in public universities, the majority focus on technology, and some are diverse (social and cultural). Some internal and external partners help them with financial support. One of the challenges (maybe the most important) is a set of constraints because some lecturers cannot understand how to use academic knowledge in consultancy. Research, Practical & Social implications – The differences found between incubator categories are in the results that lead to this business model being more complex than it is in reality. The presentation of different incubator realities and challenges focusing on the discussion of ‘selling’ knowledge, the use of public resources by private enterprises, are the practical and social implications. Originality/value - The main contribution is to show the reality of these incubators, the empirical results, adding a new perspective to the discussion. Keywords - Business incubators; Challenges; Triple Helix; Information and Communication Technology.